Helicobacter pylori immunization and atopic dermatitis in South Italian children. Issue 4 (1st August 2014) - Pedullà, Marcella; Fierro, Vincenzo; Del Tufo, Ester; Alfano, Rossella; Triassi, Maria; Perrone, Laura
Abstract : Background: The epidemiological decrease of Helicobacter pylori (Hp) infection has been recently associated to the increase of several extra‐intestinal allergic disorders. Objective: We investigated the role of specific Hp IgG production in the development of IgE or not IgE mediated food allergy (FA) in children affected by atopic dermatitis (AD). Methods: From January 2010 to July 2013, 290 South Italian children, aged between 26 and 142 months, were consecutively referred to the Pediatric Clinic of the Pediatric Department at Second University of Naples and were diagnosed as affected by AD. The patients were classified in two groups on the basis of diagnosis of food allergy (88 FA affected and 202 not FA affected) and further divided on the basis of the diagnosis of atopy (63 IgE mediated and 23 not IgE mediated). Hp serum IgG was detected using an enzyme linked immunosorbent assay (ELISA) kit (Wampole® Helicobactor pylori IgG ELISA II, Wampole Laboratories, Cranbury, NJ) and Hp stool antigens using enzyme immunoassay (Premier Platinum HpSa plus, Cincinnati OH). Results: We found a statistically significant higher prevalence of Hp serology positivity in not FA vs. FA AD‐affected children ( p  = 0.032) and a significant inverse association between FA and Hp immunization (1/OR 0.32 95% CI 0.11–0.95). Further, we identified an absolute prevalence Hp serology positivity in not‐IgE‐mediated rather than in IgE‐mediated FA AD‐affected patients ( p  = 0.0006). Conclusion: We hypothesize that specific Hp IgG production could protect against the development of both FA and atopy in AD‐affected children.